Styly vedení školy a sociální klima učitelských sborů - Andrea Rozkovcová; Jitka Novotová (Karolinum Press, 2019)
The research study introduces the most often defined leadership styles in schools presented in foreign professional research and theoretical literature which serve as a theoretical frame for the interpretation of the results of the qualitative research realized in three Czech basic schools. The aim of the qualitative research was to find out which leadership styles are used in schools with extreme parameters of the social climate of the school teaching staff. The case study approach was used, specifically interviews with leaders of the selected schools, and with carefully selected teachers, focus groups with school students and analysis of school documentation. The research shows diversity of styles and the impact on the social climate. The principal has been identified as a significant factor in creating social climate of the teaching staff. Is the principal perceived as a part of the staff? Does he or she behave the same way that they demand from the teachers? Are teachers controlled and/or do they get support from the principal? Mutual trust, cooperation and respect to opinion diversity were identified as very important factors in the relationship between the principal and the teachers.